2021
DOI: 10.1556/446.2021.30008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the single-step and double-step sous-vide treatment effect on the quality attributes of chicken breast •

Abstract: Sous-vide treatment is a modern minimal processing cooking technique that uses a single-step temperature of 55–70 °C and longer time. The quality attributes of meat might be improved by including cooking steps at below 50 °C temperatures in the sous-vide treatment. The aim of this study was to investigate the effects of the double-step sous-vide treatments on the quality attributes of the chicken breast and comparing with the traditional single-step sous-vide treatments. The single-step sous-vide treatments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Today, it is not only used alone but also in combination with other lowimpact processes, as these combined processes can reduce the food safety risk associated with the technology due to the low-temperature heat treatment. Forward-looking results have been obtained for sous-vide chicken breasts, where the temperature was increased in several steps during the heat treatment [10][11][12]. Both the texture, weight loss values, and organoleptic properties were improved compared to the single-step treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Today, it is not only used alone but also in combination with other lowimpact processes, as these combined processes can reduce the food safety risk associated with the technology due to the low-temperature heat treatment. Forward-looking results have been obtained for sous-vide chicken breasts, where the temperature was increased in several steps during the heat treatment [10][11][12]. Both the texture, weight loss values, and organoleptic properties were improved compared to the single-step treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the application of proteolytic enzyme activation temperatures as an initial stage in the sous vide processing can potentially increase chicken breast tenderness. In fact, previous studies demonstrated that a two-step sous vide method that included a temperature of 45–50 °C showed improved texture attributes of meat such as shear force, hardness, gumminess, and chewiness values compared to the traditional one-step sous vide cooking method [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%